Senam Yoga dan Aromaterapi terhadap Kualitas Tidur pada Lanjut Usia - Setiawan, Asep Widi Muharom Solih; Nurhalinah, Nurhalinah; Meilianingsih, Lia; Juniarti, Neti; Suharijiman, Suharijiman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of yoga and aromatherapy on sleep quality in older people. The research method used is a quasi-experiment with a pre-test and post-test group control design. The results showed that the sleep quality in the control group was 2.631, while the sleep quality of the experimental group was 3.723. A p-value of 0.000 (<0.05) was obtained based on statistical tests using the T-Test. In conclusion, there is a significant effect between yoga and aromatherapy on sleep quality in older people. Keywords: Aromatherapy, Sleep Quality, Elderly, Yoga